Bifurcated Halogen Bond-Driven Supramolecular Double Helices from 1,2-Dihalotetrafluorobenzene and 2,2′-Bi(1,8-naphthyridine) - Wang, Ziyu (Crystals (Basel), 2022)
The unique enantiomeric pairs of double helices have been found in the structure of the cocrystal between 1,2-diiodotetrafluorobenzene and 2,2′-bi(1,8-naphthyridine). The formation of the supramolecular double helices is driven by the strong bifurcated iodine bonds which can force the herringbone packing arrangement of the molecules 2,2′-bi(1,8-naphthyridine) into a face-to-face π···π stacking pattern. In contrast, the cocrystal between 1,2-dibromotetrafluorobenzene (or 1,2-dichlorotetrafluorobenzene) and 2,2′-bi(1,8-naphthyridine) was not obtained under the same conditions. The interaction energies of the bifurcated halogen bonds and π···π stacking interactions were computed with the reliable dispersion-corrected density functional theory. The computational results show that the bifurcated iodine bond is much stronger than the bifurcated bromine bond and bifurcated chlorine bond, and it is the much stronger bifurcated iodine bond that makes the cocrystal of 1,2-diiodotetrafluorobenzene and 2,2′-bi(1,8-naphthyridine) much easier to be synthesized.